Church life between the metropolitan and the local parishes, parishioners, and parish priests in seventeenth-century Mexico - Lundberg, Magnus, 1972- (Tiempo emulado ;, 2011)
The book is a study of parish life in central Mexico during the first half of the seventeenth century. Particular emphasis is put on the interaction between the indigenous parishioners and the secular priests working in the parishes.